Quality Dynamics of Beef Bottom Round During 2-Month Frozen Storage (−18 °C) and Week-Long Refrigeration (4 °C) - Yue Song; Wenbo Hou; Mengliu Zhu; Otobong Donald Akan; Yanxia Xing; Yang Yu; Bo Li; He Zhu (Metabolites)
Background/Objectives: The present study aimed to investigate the effects of frozen (−18 °C) and refrigerated (4 °C) storage conditions on several beef bottom round quality parameters. Methods: Fresh beef bottom round samples were stored under both frozen (−18 °C) and refrigerated (4 °C) conditions. For frozen samples, the pH, color, cooking loss, thawing loss, centrifugal loss, drip loss, moisture content, shear force, TBARS and TPA were measured at 0, 30 and 60 days. For refrigerated samples, the pH and color were analyzed at 0, 1, 3, 5 and 7 days, and the differential metabolites were also identified based on the VOCs analysis combined with multivariate statistical analysis. Results: The surface color (L*, a*, and b*) of the beef bottom round became darker during both the frozen and refrigerated periods of prolonged storage. The samples’ pH significantly declined (p < 0.05) during the frozen storage but alternated (initially reduced and then increased) under refrigerated conditions. Additionally, the frozen treatment led to a significant change (p < 0.05) in the texture profile. The thiobarbituric acid reactive substance (TBAR) values, shear force, cooking loss, thawing loss, centrifugal loss, and drip loss increased significantly with an extended frozen storage time, while the moisture content was significantly lower (p < 0.05). Moreover, nine volatile organic compounds (VOCs) were identified as potential determinants of beef bottom quality during refrigerated storage. Conclusions: The findings can contribute to a deeper understanding of quality variations during frozen storage and refrigerated storage, and provide new thoughts to improve preservation and storage strategies for the beef bottom round.